The relationship between employee attitudes and organizational performance at Jabatan Pendidikan, Bukit Beruang Melaka / Nur Farahazirah Jaafar - Jaafar, Nur Farahazirah (Faculty of Business and Management, 2018)
A workplace area is the place where employees spend most of their time with a purpose of making their job done, it is compulsory for an employee to have the ideal employees attitude where this has relationship towards job performance. The purpose of this research is to study the relationship between employees’ attitude and job performance. The study is conducted at Jabatan Pendidikan, Bukit Beruang Melaka. This study used four elements which are, job satisfaction, job motivation and job commitment as the independent variables and job performance as the dependent variable. This study involved Jabatan Pendidikan, Bukit Beruang Melaka as the respondents. This study used structural questionnaire from previous published research as the measurement for this study. A set of questionnaire was distributed to respondents and the data collected were analyzed using Statistical Package for Social Science (2.0). The data collected used as the part of sources to this research.